Next Steps in Planning - Planning Commission (Planning Commission, 1959)
This book synthesizes Professor P. C. Mahaldar’s analysis of India’s early planning experience with empirical evidence from the Ninth Round of the National Sample Survey (1955), offering a comprehensive assessment of India’s developmental challenges during the formative years of planned economic growth. It examines the evolution of Indian planning from an initial project-oriented approach to a more coherent socialist framework emphasizing heavy industrialization, employment generation, and social equity. The discussion highlights the transformative intent of the Second Five-Year Plan, its achievements in industrial capacity building, and its limitations arising from foreign exchange constraints, technological dependence, and inadequate domestic machinery production. Mahaldar critically addresses the persistent problems of unemployment, rural health deficits, and educational imbalance, arguing for integrated reforms in medical services, vocational education, and manpower planning. Complementing this macro-level perspective, the National Sample Survey findings provide micro-level insights into rural consumption patterns, revealing the dominance of basic necessities in household expenditure and the marginal allocation to health and education. Together, the analyses underscore the urgency of strengthening basic industries, expanding social services, and aligning planning mechanisms with socialist objectives to achieve inclusive and sustainable economic development in India.
Mahalanoeis, Planning Commission
Mahalanoeis, Planning Commission
Keywords: Second Five Year Plan; Planning for Socialism; Heavy Industry Strategy; Steel Production Targets; Rural Health Services; Junior Doctor Training Scheme; National Health Service Proposal; Labour Exchange Unemployment Data; National Sample Survey Ninth Round; Rural Consumption Expenditure Patterns